2000
DOI: 10.14411/eje.2000.034
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity and survival of Anagyrus kamali (Hymenoptera: Encyrtidae) under different feeding and storage temperature conditions

Abstract: Abstract. The parasitoid, Anagyrus kamali Moursi (Hymenoptera: Encyrtidae), has been recently introduced into the Caribbean as a biological control agent against the hibiscus mealybug (HMB), Maconellicoccus hirsutus Green (Homoptera: Pseudococcidae). Storage of A. kamali that is essential for its use in biological control did not affect the longevity of female and male parasitoids (40.3 ± 14.07 and 31.7 ± 9.57 days, respectively) when kept at 20 ± 2°C in absence of hosts and fed ad libitum with droplets of pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Females of all three parasitoid species outlived males. This has been recorded in other parasitoids species such as Anagyrus kamali Moursi (Sagarra et al 2000). In this study, smaller body size, lower progeny production, and shorter longevity may not have contributed to the Þeld efÞciency of A. papayae although there may be a relationship between body size and Þtness parameters for parasitoid efÞciency in other species.…”
Section: Discussionsupporting
confidence: 46%
“…Females of all three parasitoid species outlived males. This has been recorded in other parasitoids species such as Anagyrus kamali Moursi (Sagarra et al 2000). In this study, smaller body size, lower progeny production, and shorter longevity may not have contributed to the Þeld efÞciency of A. papayae although there may be a relationship between body size and Þtness parameters for parasitoid efÞciency in other species.…”
Section: Discussionsupporting
confidence: 46%
“…We chose the koinobiont endoparasitoid Anagyrus kamali Moursi (Hym., Encyrtidae) as a model for the study of the impact of mating on parasitoid fitness. Although this solitary parasitoid was recently imported from China by CABI Bioscience and released in the Caribbean to control the Hibiscus or Pink Mealybug (HMB), Maconellicoccus hirsutus Green (Hom., Pseudococcidae), little information has been published on it so far, except for M oursi (1948), M ani (1989), W illiams (1996), S agarra and V incent (1999) and S agarra et al. (2000a, b, c, d).…”
Section: Introductionmentioning
confidence: 99%
“…Sagarra et al . (2000) showed that the survival of the hymenopteran Anagyrus kamali (Encyrtidae) at 20°C was around 1.7 and 1.3 days when the parasitoids were not fed, and 40.3 and 31.7 days when they were fed (females and males, respectively). Davies et al .…”
Section: Discussionmentioning
confidence: 99%